MEMAHAMI HAKIKAT KEHIDUPAN MELALUI LIRIK LAGU KARYA BANDA NEIRA (TINJAUAN SEMANTIK: METAFORA) - Fitria Rachmawati Zain (Kajian Linguistik dan Sastra, 2021)
This scientific article examines the metaphors and meanings contained in song lyrics by Banda Neira. This writing uses a qualitative method with a semantic approach, which is focused on the metaphor of Parera. Based on data analysis, this research can be concluded from the attractiveness factor of song lyrics, the existence of meaning of life in each song's lyrics. In the lyrics of the song The Broken Growing Missing There are anthropomorphic and abstract metaphors to the concrete. Flower song lyrics there are abstract to concrete metaphors. The lyrics of the song Matahari Pagi have abstract metaphors to the concrete, anthropomorphic, and soap operas. The most dominant type of metaphor, namely abstract to conclusive metaphor. The meaning of the song lyrics by Banda Neira is the meaning of the aspect of life sacrifice.Keywords: song lyrics, Banda Neira, metaphor